If x = 3 p + 3 p 2 + p is a root of x 3 + a x 2 + b x + c = 0 , where p is a prime number and a , b , and c are integers, and if b c − a b = 1 0 0 , find the value of a + b + c + p .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great job, you found a shorter way than me!
You may not need to know that p is a prime number, but you do need to know that p is not a cube, otherwise there are multiple solutions to the cubic. For example, if p = 8 , then x = 1 4 , and that is a root of x 3 + 2 x 2 − 3 2 x − 2 6 8 8 = 0 , where b c − a b = − 3 2 − 2 6 8 8 − 2 − 3 2 = 1 0 0 .
Log in to reply
Well said.
Sir, i have solved the same way as of pi han goh . What was your method
Log in to reply
I just posted my method for you to look at.
I have solved in same way.
Let x = 3 p + 3 p 2 + p .
Then x 3 + a x 2 + b x + c
= ( 3 p + 3 p 2 + p ) 3 + a ( 3 p + 3 p 2 + p ) 2 + b ( 3 p + 3 p 2 + p ) + c
= ( 6 p 2 + 3 p ) 3 p + ( 3 p 2 + 6 p ) 3 p 2 + p 3 + 7 p 2 + p + 3 a p 3 p + ( 2 a p + a ) 3 p 2 + a p 2 + 2 a p + b 3 p + b 3 p 2 + b p + c
= ( 6 p 2 + 3 p + 3 a p + b ) 3 p + ( 3 p 2 + 6 p + 2 a p + a + b ) 3 p 2 + p 3 + 7 p 2 + p + a p 2 + 2 a p + b p + c
For the 3 p terms to cancel out, 6 p 2 + 3 p + 3 a p + b = 0 , and for the 3 p 2 to cancel out, 3 p 2 + 6 p + 2 a p + a + b = 0 , and these two equations solve to a = − 3 p and b = 3 p ( p − 1 ) for p = 1 .
Substituting a = − 3 p and b = 3 p ( p − 1 ) back into the cubic equation, c solves to c = − p ( p − 1 ) 2 .
If b c − a b = 1 0 0 , then 3 p ( p − 1 ) − p ( p − 1 ) 2 − − 3 p 3 p ( p − 1 ) = 1 0 0 , which solves to p = 1 5 1 .
If p = 1 5 1 , then a = − 3 p = − 4 5 3 , b = 3 p ( p − 1 ) = 6 7 9 5 0 , c = − p ( p − 1 ) 2 = − 3 3 9 7 5 0 0 , and a + b + c + p = − 3 3 2 9 8 5 2 .
Nice method.
Problem Loading...
Note Loading...
Set Loading...
Note that we don't need to know that p is a prime number to solve this question.
We have x − p = p 1 / 3 + p 2 / 3 , then cubing both sides gives ( x − p ) 3 = p + p 2 + 3 p ( = x − p p 1 / 3 + p 2 / 3 ) ⟹ x 3 + x 2 ( − 3 p ) + x ( 3 p 2 − 3 p ) + ( − p 3 + 2 p 2 − p ) = 0 . Thus, ( a , b , c ) = ( − 3 p , 3 p 2 − 3 p , − p 3 + 2 p 2 − p ) ⟹ 3 p 2 − 3 p − p 3 + 2 p 2 − p − − 3 p 3 p 2 − 3 p = 1 0 0 Simplifying the equation above gives p = 1 5 1 ⟹ ( a , b , c ) = ( − 4 5 3 , 6 7 9 5 0 , − 3 3 9 7 5 0 0 ) The answer is ( − 4 5 3 ) + 6 7 9 5 0 + ( − 3 3 9 7 5 0 0 ) + 1 5 1 = − 3 3 2 9 8 5 2 .